Evolution of the Veternica cave (Medvednica Mountain, Croatia) drainage system: insights from the distribution and dating of cave deposits - Damir Lacković; Bosiljka Glumac; Yemane Asmerom; Andrej Stroj (Geologia Croatica, 2011)
Detailed field examination, U-Th age dating, and stable isotope analysis of Veternica flowstone and shelfstone deposits have been employed in order to unravel details about the geological history of Veternica Cave (Medvednica Mountain, Croatia). The study was carried out in the hydrologically inactive part of the main cave channel, which is developed mainly along the unconformity between Triassic dolostone and Miocene limestone. For 180 m from the cave entrance, (located at 320 metres above sea level (asl)), the morphology of the main channel reflects exclusively phreatic conditions in the cave until the end of its hydrological activity. From 180 to 390 m, the phreatic channel has a secondary vadose entrenchment in the bottom part as marked by massive flowstones at elevations from 306 to 313.5 m asl. From 390 m farther inside the cave (in the upstream direction), the main channel has a tall, narrow cross-section and is of mainly vadose origin. In this part of the cave shelfstone precipitates are observed at 9 different levels ranging from 318.8 to 320.2 m asl, indicating the water palaeolevels in the cave. U-Th dating revealed the age of the highest shelfstone (320.2 m asl) of ~380 kyrs BP, and the age of the lowermost analyzed shelfstone (318.9 m asl) of ~245 kyrs BP. Dating of flowstone deposits, located below the shelfstone level, revealed their formation from ~235 to 205 kyrs BP. A relatively rapid water table lowering and transition from phreatic to vadose conditions occurred within the cave, from ~245 to 235 ka BP, between formation of the youngest shelfstone (representing phreatic conditions below their level) and the oldest flowstone (marking the beginning of vadose conditions). The results provide unique new information about Veternica Cave genesis and geomorphologic evolution of the Medvednica Mountain area.